Effectiveness of Soursop Leaf Extract (Annona muricata l.) on IL-6 Levels in Mammary Sprague dawley Female Rats Induced by Staphylococcus aureus - Purnamasari, Feby; Yulianty, Risfah; Latief, Syamsa (Universitas Negeri Semarang in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)))
Research this aiming for analyze effectiveness extract leaf soursop could take effect to IL-6 levels at mammae rat female Sprague Dawley induced Staphylococcus aureus. Research this use type research Experiment Moot or quasi-experimental design with the design of the Post-test Only Control Group Design by looking at the 3th and 6th day IL-6 levels after induction bacteria Staphylococcus aureus and giving treatment on mammae rat female Sprague Dawley. Taking sample blood done at eye rat 2 times with examination elisa kit. Data analyzed with use Hock and Post test followed by the Mann Whitney test . Research results to show that not there is difference IL-6 levels at group control (?=0,062 > ? =0,05) and group antibiotics (?=0,0514 > ? =0,05). On group leaf soursop (?=0.037 < ? =0,05) and group antibiotics + leaves soursop and on group control (?=0.030 < ? =0,05) to show there is difference levels IL-6. Value mean on group soursop 7.50 ± 1.74 pg/ml day to3, and 7.50 ± 1.74 1 pg/ml day 6. Value mean on group soursop + antibiotics 7.46 ± 26t.66 pg/ml Day 3, and 4.73 ± 1.36 pg/ml day 6. The implication of this study is that soursop leaf extract or combination of antibiotic + soursop leaf extract can be as a complementary therapy for mastitis caused by the bacteria Staphylococcus aureus. Keywords: Extract Leaf Soursop, Levels IL-6, Rat Sprague Dawley Females